A Simulation Design of Immersive Virtual Reality for Animal Handling Training to Biomedical Sciences Undergraduates - Tang, Florence Mei Kuen; Lee, Ray Mau Fung; Szeto, Roy Hok Lai; Cheng, Jason Ka Kit; Choi, Frederic Wai To; Cheung, Justin Chak Ting; Ngan, Olivia Miu Yung; Lau, Ann Sin Nga (Frontiers in Education, 2021)
Background One area of biomedical research concerns is applying new treatments to cure human diseases, moving bench-side research to the bedside practice. While using animal models is crucial in the research process, researchers should strictly adhere to the moral 4R framework to protect animal welfare — replacement, reduction, refinement, and responsibility. Virtual reality (VR) applies computer technology to create a simulated environment, allowing players to immerse and interact with animated 3D contexts. We developed a virtual animal-holding simulator (ViSi) using immersive virtual reality technology for students studying in the undergraduate biomedical sciences programme. The specific objectives of the paper are to (1) describe the development of the VR courseware for animal training and (2) describe the learning experience among students. Method and Result An evaluation of the courseware was conducted among Year 1 and 2 biomedical sciences students. Students who participated in ViSi responded positively about their involvement in the virtual environment experience and their concentration on the assigned task. Discussion ViSi is a reliable simulation technology that can train animal handling skills, which replaces real animals, while learners’ multi-cognition could still be enhanced with simulation training. Thus, the impact of immersive VR technology integrated into skills training is promising, although few technical problems are to be resolved.